Comparative diagnostic accuracy of ultrasound and chest radiography in ETT tip localization - Widyaningtiar, Hapsari; Prawira, Yogi (Paediatrica Indonesiana, 2025)
Background Endotracheal intubation is a life-saving intervention, and accurate placement of the endotracheal tube (ETT) is crucial in pediatric patients due to anatomical variability. Ultrasound offers a practical and safe alternative to chest X-ray (CXR) for verifying ETT placement. Objective To compare the diagnostic accuracy of ultrasound compared to CXR in localizing the ETT tip in pediatric patients. Methods A cross-sectional study was conducted from January to April 2025 in the Pediatric Intensive Care Unit and Cardiac Intensive Care Unit at Dr. Cipto Mangunkusumo Hospital. The study included children aged 1 month to 18 years intubated with either cuffed or uncuffed ETTs. A CXR was performed immediately after intubation, followed by ultrasound within 24 hours. ETT position was assessed based on CXR findings and tracheal ring alignment on ultrasound. Results A total of 89 patients were enrolled. Ultrasound demonstrated sensitivity of 88.6%, specificity of 73.7%, overall accuracy of 85.4%, positive predictive value (PPV) of 92.5%, and negative predictive value (NPV) of 63.6%. The area under the receiver operating characteristic curve (AUC) was 0.811. The positive likelihood ratio (LR+) was 3.37, and the negative likelihood ratio (LR–) was 0.16. Multivariate analysis identified ultrasound as a significant predictor of accurate ETT placement [odds ratio (OR) 7.75; 95%CI 1.29 to 4.74; P<0.001]. Conclusion Ultrasound is a feasible, reliable and accurate alternative to CXR for verifying ETT tip positioning in pediatric intensive care settings.